Unsafe work practices and work-related stress in motorcycle repair shops: A cross-sectional analysis - Kurnia, Fikrihadi; Suartika, I Made (Universitas Sultan Ageng Tirtayasa, 2025)
Background: Motorcycle repair shops in developing economies often operate with inadequate safety standards, exposing workers to health and safety hazards. This study aimed to investigate the relationship between unsafe work practices and work-related stress among motorcycle mechanics in Lombok, Indonesia. Methods: A cross-sectional study design was employed, with data collected using self-administered questionnaires from a sample of 148 male motorcycle repair workers. Descriptive statistics, validity and reliability testing, and Chi-Square tests, used to analyze the data. Results: The study found a significant association between working while visibly sick (presenteeism) and elevated stress levels. Additionally, working while visibly fatigued was also associated with increased stress. Discussion: These findings highlight the detrimental impact of presenteeism and fatigue on worker well-being within the motorcycle repair industry. The lack of association with other unsafe practices suggests that additional workplace stressors may be influential in this setting. Conclusions: Employers in the motorcycle repair industry should prioritize policies that discourage working while sick and promote adequate rest to mitigate stress and potential safety risks. Further research, including qualitative methods and diverse samples, is needed to fully understand the complex interplay between unsafe practices, stress, and other workplace factors affecting worker well-being.